2016
DOI: 10.1177/1541204015579522
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation in Juvenile Arrestees

Abstract: Mental health screening data (Massachusetts Youth Screening Instrument version 2 [MAYSI-2]) and offense history were used to study levels of suicidal ideation in a sample of juvenile arrestees held in a large, urban detention center located in a predominately Hispanic Southwestern U.S. city. We used t-tests and multinomial logistic regression to examine the relationships with particular attention to temporal issues. Results indicated that offense history, the timing of arrests, and demographics did influence l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Across the juvenile justice system, studies reported past year suicide ideation ranging from 19%-50%; in comparison to high school youth who ranged from 12%–16% (Kemp et al, 2021; Wasserman & McReynolds, 2006) (for a review see Teplin et al, 2002). This includes arrest populations, where an arrest experience was associated with suicide ideation among youth and young adults (Ahuja et al, 2021; Tapia et al, 2002). Worse general health is also common among arrested populations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Across the juvenile justice system, studies reported past year suicide ideation ranging from 19%-50%; in comparison to high school youth who ranged from 12%–16% (Kemp et al, 2021; Wasserman & McReynolds, 2006) (for a review see Teplin et al, 2002). This includes arrest populations, where an arrest experience was associated with suicide ideation among youth and young adults (Ahuja et al, 2021; Tapia et al, 2002). Worse general health is also common among arrested populations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous evidence indicated the significance of this age-specific maladaptive trait perspective for a better understanding of specific mental health problems in youth such as autism spectrum symptoms (De Clercq et al, 2010), obsessive-compulsive symptomatology (Aelterman et al, 2010), severe conduct problems (Frick et al, 2014) and relational aggression (Tackett et al, 2014). From this evidence, it can thus be hypothesized that such maladaptive trait perspective may also be valuable to gain a better understanding of individual differences in highly prevalent mental health problems in detained youth (Stathis et al, 2008), such as alcohol/drug use (Chassin, 2008), posttraumatic symptoms, anger/irritability, depression/anxiety, somatic complaints, and suicide ideation (Tapia et al, 2016;Wasserman et al, 2004).…”
Section: Gender Differences In Psychopathology Among Detained Youth F...mentioning
confidence: 99%
“…In addition, JJS-involved youth typically report histories of trauma and victimization (Abram et al, 2004, 2007; Ford et al, 2013), childhood maltreatment (King et al, 2011), suicidality (Abram et al, 2008; Tapia et al, 2016; Teplin et al, 2015), and self-injury (Chapman & Ford, 2008; Ford et al 2010). JJS-involved youth are vulnerable to the human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs) because of their risky sexual activities (Donenberg et al 2015).…”
Section: Introductionmentioning
confidence: 99%